Development and characterization of screen-printed Prosopis Africana char thick film for electronic applications - Babani, Suleiman; Hamidon, Mohd Nizar; Ismail, Alyani; Jaafar, Haslina; Hassan, Intan Helina; Shafiee, Farah Nabilah; Yunusa, Zainab; Lamido, Jamila; Bakar, Azlinda Abu; Lawal, Ismail; Shitu, Ibrahim Garba (Springer, 2024)
The need for biomass materials that are both cost-effective and highly effective has increased rapidly in a number of areas, including flexible electronics. The aim of this research is to investigate the properties of a screen-printed thick film of Prosopis Africana charcoal (PAC) on an alumina substrate. The biochar was obtained from the Prosopis Africana strain by subjecting it to controlled pyrolysis at 500 °C for 3 h. The rheological properties of the PAC pastes were formulated at a powder-to-organic binder ratio of 40:60 wt%. An average 11.8-µm-thick layer was produced using the screen-printing process. X-ray diffraction analysis showed the presence of characteristic peaks at approximately 25.0° and 44.7°. These peaks correspond to the (002) and (004) reflections of the graphite structure. Thermogravimetric analysis revealed that the PAC film exhibited thermal stability in an airflow environment up to 650 °C. The surface morphology of the PAC thick film exhibits a reticulated appearance with patchy features, while elemental composition analysis (EDX) confirmed the high carbon content of the PAC thick film. The real and imaginary dielectric constants of the PAC thick film at 10 GHz were found to be 9.8 and 1.8, respectively. It can be concluded that the PAC biochar has promising electronic properties, making it a suitable candidate as an environmentally friendly material for a range of electronic applications.